(untitled) (Heritage, 2024)
Due to the global spread of new technologies and communication channels, today’s students are increasingly engaged in multimodal content and are significantly exposed to digital information on a daily basis. As a result of the aforementioned, there has been a significant increase in the research of scientific publications on multimodal teaching practices and the effects of such teaching practices on student learning. This is where new work methods and new pedagogies similar to multimodal pedagogy appear. In the context of foreign language teaching, the use of multimodality and multimodal pedagogy to stimulate students can improve their interest in learning and memory, bearing in mind that multimodal texts use different modes of communication, with specific modes or a combination of modes, and offer opportunities to create multiple meanings. Hence, the process of reading and writing multimodal texts takes place in a more interactive way than is the case with modal and printed texts. With the help of modes, learning foreign languages becomes creative, analytical, active, investigative and contributes to the development of students’ critical thinking. The aim of the work is precisely to point out the importance of multimodal pedagogy and the approach that includes working with multimodal texts in the context of foreign language learning.